Surface site modulations by conjugated organic molecules to enhance visible light activity of ZnO nanostructures in photocatalytic water splitting - George, Leena; Sappati, Subrahmanyam; Ghosh, Prasenjit; Devi, R. Nandini (Journal of Physical Chemistry C, 2015)
Surface modification of ZnO nanoparticles is identified as a method of modulating surface sites advantageously. ZnO nanoparticles of two different sizes are surface modified with a conjugated organic moiety to enable electron conduction and transfer. Enhanced H-2 evolution from water-methanol mixtures was observed in the composite systems compared to pristine ZnO under visible light irradiation without any cocatalyst. The system is also marginally active in water splitting in pure water without any sacrificial agents. Photophysical characterization indicates that even though reducing size into the nanoregime affects the band gap detrimentally, modifications by simple conjugated organic molecules assist in enhanced visible light activity. The experimental observations are corroborated with computational studies, which also point to a localization of valence band maximum of the interface on the organic moiety and conduction band minimum on ZnO.